Fire safety of bridges – methodology supporting design and forensic evaluation. Issue 1 (January 2017) - Yanagisawa, Norifumi; Imagawa, Yusuke; Ohyama, Osamu; Rutner, Marcus; Kurita, Akimitsu
Abstract: Dedicated to Prof. Dr. Eng. Akimitsu Kurita on his 70th birthday, in honour of his scientific achievements, guidance and the education of his students. Fire safety in bridge design is not as developed as fire safety in building design, even though a bridge failure can cause significant economic damage impacting on an area. This paper addresses an unanswered question with regard to fire safety, i.e. the capability to identify the governing failure mode of a bridge subjected to severe fire loading and ranking the regions of greatest fire exposure risk. Hence, this proposed methodology is also expected to support forensic work identifying the failure mode where a bridge has failed due to a severe fire, as will be shown using the 9‐Mile Road Overpass collapse as an example. In an effort to mitigate fire damage, the fire protection panel (FFP) is introduced, which is part of a sacrificial structure shielding the bridge superstructure from exposure to fire from underneath.